Elimination of Heavy Metal bythe Adsorption Process on Activated Carbon from Olive Pomace - Nait Merzoug, A.; Bellazi, M.I.; Guellati, O. (Algerian Journal of Research and Technology (AJRT), 2017)
Wastewater pollution by heavy metals remains one of the major problems to be solved throughout the world. Various conventional methods are used to remove heavy metals from existing wastewater. They are based on phenomena of chemical precipitation, ion exchange or adsorption, which is always the simplest and most effective technique. Our work has a dual environmental aspect; On the first hand a valorization of a natural by-product in this case the olive-pomace collected in the region of Souk Ahras (East Algeria) and on the other hand the study of the adsorption of lead on this biomaterial. The activated carbon obtained after calcination and chemical activation has undergone a whole range of physicochemical analyzes such as: pH, moisture content, elementary analysis, surface area and infrared spectrometry. Indeed, the efficiency of our adsorbent is evaluated through the study of the various parameters that affects the adsorption phenomenon, namely: contact time, mass of the adsorbate, temperature, pH and initial concentration metal. The results obtained have shown a good efficiency of our support for the adsorption of metal ions in aqueous solution.